The Effect of Information Technology and Performance Appraisal on Employee Performance with Motivation as an Intervening Variable - William Korintius Sianturi; Wawan Prahiawan; Ali Imron; Vera Maria (Indonesian Journal of Innovation Multidisipliner Research, 2025)
This study examines the effects of Information Technology and Performance Appraisal on Employee Performance, with Motivation as an intervening variable, using a descriptive quantitative method and saturation sampling involving 80 respondents. Data was gathered via a questionnaire with an interval scale and analyzed using SmartPLS software. The results indicate that Information Technology positively and significantly impacts Employee Performance and Motivation, Performance Appraisal positively and significantly influences Employee Performance and Motivation, and Motivation positively and significantly affects Employee Performance. Additionally, Motivation mediates the relationship between Information Technology and Employee Performance, as well as between Performance Appraisal and Employee Performance.